Examining the relationship between balance confidence and the physical and psychosocial adaptation to transtibial amputation on physical activity participation and avoidance habits - Hudson, Lucas W. (My University, 2022)
Transtibial amputation (TTA) is the removal of the lower leg at the tibia and often results in pain, mental health issues, and reduced quality of life. Many of these symptoms are created or exacerbated by a sedentary lifestyle, and a lack of physical activity (PA). Less than 40% of people with TTA participate in PA. It has been speculated that people with TTA who have low balance confidence may actively avoid PA to avoid falling and the associated pain that comes with it. This relationship has been detected in people with lower extremity amputation where they avoid stressors in general, but not in an exclusively TTA population or in the context of PA. Alternatively, other factors related to the physical and psychosocial adaptation to amputation such as depression, anxiety, or impaired mobility may be responsible for the avoidance of PA in people with TTA. The exercise avoidance patterns of people living with TTA has received little research. As such, the purpose of this study was to explore the relationship between balance confidence and the physical and psychosocial effects of TTA and how this related to PA participation and avoidance habits.
Keywords: Transtibial amputation; Physical and psychosocial benefits (physical activity)